Use and cost of disease-modifying therapies by Sonya Slifka Study participants: has anything really changed since 2000 and 2009?. Issue 1 (February 2019) - Minden, Sarah L; Kinkel, R Philip; Machado, Helene T; Levin, Jonathan S; Rosenthal, Meredith B; Iezzoni, Lisa I
Background: Disease-modifying therapies benefit individuals with relapsing forms of multiple sclerosis, but their utility remains unclear for those without relapses. Objective: To determine disease-modifying therapy use and costs in 2009, compare use in 2009 and 2000, and examine compliance with evidence-based guidelines. Methods: We determined the extent and characteristics of disease-modifying therapy use by participants in the Sonya Slifka Longitudinal Multiple Sclerosis Study (Slifka) in 2000 ( n =2156) and 2009 ( n =2361) and estimated out-of-pocket and total (payer) costs for 2009. Two multivariable logistic regressions predicted disease-modifying therapy use. Results: Disease-modifying therapy use increased from 55.3% in 2000 to 61.5% in 2009. In 2009, disease-modifying therapy use was reported by 76.5% of participants with relapsing-remitting multiple sclerosis, 73.2% with progressive-relapsing multiple sclerosis, 62.5% with secondary progressive multiple sclerosis, and 41.8% with primary progressive multiple sclerosis. Use was significantly associated with relapsing-remitting multiple sclerosis, shorter duration of illness, one to two relapses per year, non-ambulatory symptoms, using a cane, younger age, higher family income, and having health insurance. Average annual costs in 2009 were US$939–3101 for patients and US$16, 302–18, 928 for payers. Conclusion: Use rates were highest for individuals with relapsing-remitting multiple sclerosis, but substantial for those with progressive courses although clinical trials have not demonstrated significant benefits for them.